Dampak Reformasi Birokrasi pada Perubahan Budaya Organisasi di Perwakilan BPKP Provinsi DKI Jakarta - Aridhona, Nina; Baga, Lukman M.; Affandi, M Joko (Jurnal Manajemen dan Organisasi, 2015)
Various changes in the strategic environment have forced the public sector to make bureaucratic reform that should have consequences on changing the bureaucratic culture in the public sectorsto be more externally oriented culture. Financial and Development Supervisory Agency (BPKP) is an internal control government agency that should change the organizational culture. The needsforexternally oriented culture was now even stronger in line with the shift in the role from watchdog to become in-house consultant. Therefore, this study aims to analyze organizational culture changes and identify the factors that cause or inhibit changes. This study used competing values framework, a method that is able to capture the changes of organizational cultures, both large and direction. The research result showed that organizational culture has been transformed from hierarchy culture to market culture. These changes indicatedthe organizational culture has been changed in accordance with the concept of bureaucratic reform. However, the changes in organizational culture were not significant. Employee resistance and the policy of change that is not the same in all aspects of organizational were known as the factors inhibiting organizational culture changes.Key word: bureaucratic reform, competing values framework, organizational change, organizational culture, public sector